Learning of and with Robotics, some experiences - López Ramírez, Pedro Antonio (2013)
This paper analyzes some experiences, previously reviewed in literature, about the use of robotics in education in order to obtain relevant models for the design of a proposal about robotics learning at Basic Secondary and Middle education levels. Two scopes of application of robotics in education are considered: firstly, learning robotics by defining the context of each robot subsystems and then creating robots for different purposes. The objective in this case is the development of skills for the design and construction of robotic artifacts, a process that implies the acquisition of the necessary knowledge to accomplish this task. The second scope of application is the use of robotics to encourage knowledge construction in different areas, fostering students’ development ok skills and competences. Learning robotics and learning with robotics can be supported by computer science since this area provides software technology and tools such as Math Modeling and language simulation, Multimedia Tutorials, Virtual and Remote laboratories, among others. The purpose of this article is to highlight the importance of robotics in the classroom to enrich learning strategies which contribute to student’s comprehensive education. This field of study has a growing demand by teachers and researchers, and stimulus to encourage its research, development and spread.